2017
DOI: 10.1108/sef-10-2015-0249
|View full text |Cite
|
Sign up to set email alerts
|

Determination of China’s foreign exchange intervention: evidence from the Yuan/Dollar market

Abstract: This article is c Emerald Group Publishing and permission has been granted for this version to appear here (http://dro.dur.ac.uk/17273/). Emerald does not grant permission for this article to be further copied/distributed or hosted elsewhere without the express permission from Emerald Group Publishing Limited. Additional information:Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In addition, underpinned by the assumption that the central banks can intervene by adjusting short-term interest rates, Klaassen and Jager (2011) include interest rate differentials in calculating EMP. However, we do not include interest rate differentials because China rarely utilizes interest rate instruments to intervene in the FX market (Das, 2019;Li et al, 2017).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, underpinned by the assumption that the central banks can intervene by adjusting short-term interest rates, Klaassen and Jager (2011) include interest rate differentials in calculating EMP. However, we do not include interest rate differentials because China rarely utilizes interest rate instruments to intervene in the FX market (Das, 2019;Li et al, 2017).…”
Section: Datamentioning
confidence: 99%
“…Moreover, the intervention might not be fully reflected in changes in China's FX reserves, especially after the complete abolition of the mandatory FX settlement regime in April 2012. As documented in Li et al (2017) and Das (2019), and more recently in The Economist (2020), China has many tools to intervene in the FX market and prefers to do so by adjusting the central parity rate and other non-transparent measures rather than intervening directly, especially after 2015. The central parity rate has been a usual tool since the People's Bank of China (PBoC), China's central bank, first announced it on August 11, 2015.…”
Section: Datamentioning
confidence: 99%
“…Their study on the German central bank shows a high sterilization coeffi cient (−0.74) with a lower off set coeffi cient (−0.22), showing the eff ectiveness of sterilization with an independent monetary policy. Because of the theoretical dominance of this study, later studies (e.g., Chang et al, 2015;Li et al, 2017;Ouyang et al, 2010;Ouyang and Rajan, 2011;Zhang, 2012) followed the same framework for estimating sterilization and off set coeffi cients in the case of Asian countries. Examining the Turkish sterilization between 1990 to 1996, Denizer et al (1999) found that the sterilization was incomplete (−0.37) by contradicting the fi ndings of Altinkemer (1998).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They show evidence that the central banks took an aggressive stance against upward pressures in sharp contrast with their sluggish attitude towards depreciation. Similarly, [19] point out that PBOC acted regularly in the forex after the financial crisis to carry out asymmetric interventions in Chinese yuan owing to a 'fear of appreciation'. On the other hand, identical intervention seems to trigger asymmetric consequences.…”
Section: Literature Reviewmentioning
confidence: 99%